The Unexplored Anticaries Potential of Shiitake Mushroom - Avinash, J.; Vinay, S.; Jha, Kunal; Das, Diptajit; Goutham, B. S.; Kumar, Gunjan (Pharmacognosy Reviews)
Keeping an eye the escalating costs of dental services, the treatment cost of the consequences of dental caries can be reduced to manageable proportions by preventive measures aimed at decreasing the prevalence. One such measure is by increasing the consumption of caries preventive foods. Recently, there has been an upsurge of interest in mushrooms not only as a healthy food but also as a caries preventive food. The most common type of mushroom, Lentinula edodes also called as shiitake, is studied in‑depth for its oral health benefits. The cultivation of shiitake dates way back to 1100 A.D. during the rule of Sung dynasty which is replaced by more modern and efficient sawdust substrate log cultures lately. Shiitake mushroom extract can be isolated in various forms such as freeze dried, oil, and ethyl acetate extracts. Various biologically active compounds such as erythritol, copalic acid, adenosine, carvacrol, and many more are responsible for this mushroom’s antimicrobial activity. Anticariogenicity can be attributed to the induction of the detachment of cariogenic microorganisms from hydroxyapatite, changes in cell surface hydrophobicity, bactericidal activity, and disruption of signal transduction in Streptococcus mutans as proved through various in vivo and in vitro studies. Apart from these benefits, it has tremendous potential to be used as an antioxidant, anticancer, antigingivitis, antifungal, and antiviral agent. The one and only known adverse reaction due to shiitake mushroom consumption is the eruption of pruritic erythematous papules termed as shiitake dermatitis. This review highlights the unexplored anticaries potential of one such useful bioactive metabolite‑shiitake mushroom.
Keywords: Extract; functional foods; oral health; shiitake mushrooms